1987
DOI: 10.1111/j.1465-7295.1987.tb00723.x
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Money on Short‐term Interest Rates

Abstract: This study reviews empirical evidence from four research methods related to the impact of money on short-term nominalrates. The studies consistently fail to find evidence supporting the much hypothesized short-term, negative relationship between money and nominal rates since at least April 1975. Reasons for the absence of a negative relationship include the tendency of financial markets to anticipate corrective action by the Fed whenever M1 deviates from targeted growth ranges and a rapid adjustment of inflati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
1

Year Published

1992
1992
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(29 citation statements)
references
References 33 publications
0
28
1
Order By: Relevance
“…The first one usually identifies the monetary policy shocks as innovations to some monetary aggregate, the monetary base, the money stock or M2 [Barro (1977), Reichenstein (1987), Cochrane (1994)]. The second trend, interprets policy shocks as innovations to the baseline interest rate [Bernanke and Gertler (1995), Bernanke and Blinder (1992), Evans (1994, 1999)].…”
Section: Responses To Policy Shocks: the Evidencementioning
confidence: 99%
See 1 more Smart Citation
“…The first one usually identifies the monetary policy shocks as innovations to some monetary aggregate, the monetary base, the money stock or M2 [Barro (1977), Reichenstein (1987), Cochrane (1994)]. The second trend, interprets policy shocks as innovations to the baseline interest rate [Bernanke and Gertler (1995), Bernanke and Blinder (1992), Evans (1994, 1999)].…”
Section: Responses To Policy Shocks: the Evidencementioning
confidence: 99%
“…The applied literature on the monetary transmission mechanism mostly analyses the American case and European countries, identifying the actions of the monetary authority as a shock to either some monetary aggregate [Barro (1977), Reichenstein (1987), Cochrane (1994)] or to the baseline interest rate [Bernanke and Gertler (1995), Bernanke and Blinder (1992), Evans (1994, 1999), Peerman and Smets (2001)]. For the Brazilian case, Mendonça (2001) discusses the monetary and lending channels of monetary policy and provides an application of the Taylor's rule to the determination of the interest rate after 1999.…”
Section: Introductionmentioning
confidence: 99%
“…21 The price puzzle occurs when contractionary monetary policy shocks produce a positive response of the price level (Sims, 1992). The liquidity puzzle refers to shocks in monetary aggregates leading to an initial rising rather than falling of interest rates (Reichenstein, 1987).…”
Section: A1 Omitted Proofsmentioning
confidence: 99%
“…Second, if the point-identified model can be considered a reasonable benchmark, the method offers a simple and flexible way to add non-dogmatic identifying information to the set-identified model, which results in increasing informativeness of the conclusions in a transparent manner. Third, the method can be used to perform reverse engineering exercises that compute the prior probability one would need to attach to a set of identifying assumptions in order for the averaging to preserve a given empirical conclusion (e.g., the so-called price and liquidity puzzles in monetary SVARs, respectively discussed by (Sims, 1992) and (Reichenstein, 1987)). …”
Section: Introductionmentioning
confidence: 99%
“…For instance, using a sample period from 1973-1979, Melvin (1983 showed that, by the second month, the interest rate rose sharply above the initial rate after an increase in monetary growth. Similarly, using a sample period of quarterly data covering 1975data covering :4 -1983data covering :3, Mishkin (1981data covering , 1982 and Reichenstein (1987) also failed to find evidence supporting a short-term liquidity effect. Mehra (1985), in a study using data from both low and high inflation periods, found that a liquidity effect occurred in the 1950s and early 1960s, but this effect had all but disappeared in the subperiod beginning in the 1970s and ending in 1979.…”
Section: Introductionmentioning
confidence: 99%